Source and coefficient identification problems for the wave equation on graphs. (31st October 2018) - Avdonin, Sergei; Bell, Jonathan; Mikhaylov, Victor; Nurtazina, Karlygash
Abstract : Avdonin and Kurasov proposed a leaf peeling method based on the boundary control to recover a potential for the wave equation on a tree. Avdonin and Nicaise considered a source identification problem for the wave equation on a tree. This paper extends the methodology to the wave equation with unknown potential and source distributed parameters defined on a general tree graph.